Abdominopelvic sarcoma of perivascular epithelioid cells. Report of four cases in young women, one with tuberous sclerosis - Bonetti, F.; Martignoni, G.; Colato, C.; Manfrin, E.; Gambacorta, M.; Faleri, M.; Bacchi, C.; Sin, V. C.; Wong, N. L.; Coady, M.; Kwok-cheung, J. C. (Nature Publishing Group, 2001)
The perivascular epithelioid cell has been proposed to be the unifying proliferating cell type in a number of lesions such as angiomyolipoma, lymphangiomyomatosis, clear cell sugar tumor and renal capsuloma. With the exception of rare examples of angiomyolipoma, they are non-metastasizing. We report four examples of a new member of this family of perivascular epithelioid cell neoplasms that occur in abdominopelvic location and show metastatic properties. The patients, all women, were aged 19 to 41 years (mean, 32), and presented with a tumor mass involving the serosa of the ileum, uterus or pelvic cavity. Morphologically, the tumors were composed of sheets of large polygonal cells with glycogen-rich clear or eosinophilic cytoplasm and moderately pleomorphic nuclei, traversed by a delicate vasculature, mimicking clear cell carcinoma. There were areas of coagulative necrosis and occasional mitotic figures. Intracytoplasmic brown pigment was present in two cases. Spindly cells, smooth muscle and fat were absent. Lymphovascular invasion was present in all, lymph node metastasis was documented in two and metastasis to the ovary was present in one case. Two patients developed widespread metastatic disease after 10 and 28 months from diagnosis. One patient showed the clinical signs of tuberous sclerosis. In spite of the epithelial-like appearance, the tumor cells were negative for epithelial markers but were strongly positive with the melanogenesis-related marker HMB45. Another melanogenesis marker (MART-1) was positive in two cases. Other markers including S-100 protein, vimentin, muscle-specific actin, desmin and chromogranin A were negative. Thus, these tumors are not readily classifiable in the existing schema of known entities, and show over-lapping morpho-phenotypic features of clear cell sugar tumor of the lung and epithelioid angiomyolipoma. We consider them as sarcomas composed of a pure population of uncommitted perivascular epithelioid cell, that lack modulation toward smooth muscle or adipose cells.
Keywords: perivascular epithelioid cell; angiomyolipoma; clear cell sugar tumor; melanoma markers; tuberous sclerosis